Green Buıldıng Desıgn wıth Natural Insulatıon Materıals Produced From Cellulose for Envıronmental Pollutıon Management: The Case of Bulanık Dıstrıct - Arı, İlknur; Balo, Figen (Muş Alparslan Üniversitesi, 2024)
In this study, a green building with energy performance was designed according to the climatic conditions of the region in Bulanık district of Muş province. In the green building, cellulose-based insulation materials, whose technical values have been specified and approved for use by previous researches, were used. Twenty-four different alternative scenarios were created by combining four different cellulose-based insulation materials (amorphous cellulose, cellulose, recycled cellulose, and nano-cellulose fiber) and six different building materials (briquette, brick, block pumice, aerated concrete, concrete block, and hollow brick), taking into account the optimum insulation thickness value previously determined in the literature according to the climatic conditions of Muş province. All alternative scenarios were applied to the sandwich wall structure. A vineyard house was designed in the IES-VE simulation program in order to determine the energy efficiency and emission values affecting environmental pollution of all types obtained with material combinations. The IES-VE simulation program was used to determine the energy consumption and the amount of emissions that can be emitted to the environment for all alternative types of the vineyard house designed in Bulanık district.

Bu çalışmada, Muş iline bağlı Bulanık ilçesinde bölgenin iklim şartlarına göre enerji performanslı bir yeşil bina tasarlanmıştır. Yeşil binada daha önce yapılan araştırmalarla teknik değerleri belirtilmiş ve kullanıma uygunluğu onaylanmış selüloz esaslı yalıtım malzemeleri kullanılmıştır. Muş ili iklim şartlarına göre daha önce literatürde belirlenmiş optimum yalıtım kalınlık değeri dikkate alınarak dört farklı selüloz esaslı yalıtım malzemesi (amorf selüloz, selüloz, geri dönüştürülmüş selüloz, ve nano-selüloz fiber) ve altı farklı yapı malzemesi (briket, tuğla, blok Bims, gaz beton, beton blok ve içi boşluklu tuğla) kombine edilerek yirmi dört farklı alternatif senaryo oluşturuluştur. Oluşturulan tüm alternatif senaryolar sandviç duvar yapısına uygulanmıştır. Malzeme kombinasyonlarıyla elde edilen tüm tiplerin enerji verimliliği ve çevre kirliliğine etki eden emisyon değerlerinin belirlenmesi amacıyla IES-VE simülasyon programında bir bağ evi tasarlanmıştır. Bulanık ilçesinde tasarlanan bağ evinin IES-VE simülasyon programı ile tüm alternatif tipler için enerji tüketimi ve çevreye yayabileceği emisyon miktarları belirlenmiştir.
Çevre Kirliliği Yönetimi İçin Selülozdan Üretilmiş Doğal Yalıtım Malzemeleriyle Yeşil Bina Tasarımı: Bulanık İlçesi Örneği
Keywords: Ecology; Sustainability and Energy; Ekoloji; Sürdürülebilirlik ve Enerji